2020
DOI: 10.1021/acsomega.0c03388
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Fulvic Acid from Lignite and Characterization of Its Functional Groups

Abstract: Fulvic acid (FA) is a complex organic mixture composed of small molecules. The structure and composition of FA vary greatly because of the different raw materials used for preparing FA. In this work, FA was extracted from shallow lowrank lignite by hydrogen peroxide (H 2 O 2 ) in a microwave field, and the functional groups of FA were characterized. The optimal extraction process was determined, with the H 2 O 2 concentration being the key factor affecting the yield of FA. Thermogravimetric analysis showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…In general, all methods for FA extraction are in one package with the HA employing the alkaline solution as extracting agent, pH adjustment, and centrifugation. Gong et al (2020a) as shown in Table 3, have outlined different extraction methods of FA. Based on techno-economical aspects, some methods were considered inefficient because of the time required.…”
Section: Extraction Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, all methods for FA extraction are in one package with the HA employing the alkaline solution as extracting agent, pH adjustment, and centrifugation. Gong et al (2020a) as shown in Table 3, have outlined different extraction methods of FA. Based on techno-economical aspects, some methods were considered inefficient because of the time required.…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Besides, as this process employs high amounts of sodium (Na + ) or potassium (K + ) ions in the process, it is hard to get FA with high purity by using this technique and the use of a large volume of alkali and acid, it is considered as a nonenvironmentally friendly method. (dimodifikasi dari Bannach-Sczott & Debska, 2008) Lately, Gong et al (2020a) described a novel method for FA extraction from low-quality lignite by using hydrogen peroxide (H2O2) in a microwave apparatus that was later modified by . By using oxidizing of the material approach, the researchers have been able to develop a fast and relatively simple extraction procedure to obtain less-cation-contaminated FA.…”
Section: Extraction Methodsmentioning
confidence: 99%
See 3 more Smart Citations